Determinants Of Customer Usage Of Online Services Via Internet (WWW): A Study On TM Customer Self Service Portal - Zaid, Dina Najihah (2008)
A number of theoretical framework/models have been constructed in various studies to figure out how and why individuals adopt new information technologies. Venkatesh et al.(200) in his research has identified eight of the theoretical models. There are a number of determinants identified in various studies but the four determinants selected and used in this study are performance expectancy, effort expectancy, social influence and facilitating condition.